CABLE-AGING MANAGEMENT PROGRAM IMPLEMENTATION IN NUCLEAR POWER PLANTS - Pirc, Marko; Avsec Jurij (Journal of Energy Technology, 2024)
As a requirement for nuclear power plant life extension beyond 40 years, some additional Aging Management Programs (AMP) for passive equipment have to be implemented. This article presents an overview of Cable-Aging Management Program (CAMP) activities. The program defines basic rules and initial activities for the identification of adverse operation environment parameters that could lead to the accelerated aging of specific materials. Samples of cables are selected based on nuclear safety and electrical equipment criticality for inspection and testing, to check functionality and prevent unexpected failure during normal operation. Acceptance criteria for environment parameters and diagnostic testing have been set. Initial visual inspection of cable conditions in an adverse environment and testing of sampled cables and environment yield results for on-time preventive measures. The first cable aging management program in Slovenia has been operating since 2010, and its experience could be adapted to other companies for which cables are key components.